The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1073/pnas.1800777115
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous boron oxide at megabar pressures via inelastic X-ray scattering

Abstract: Structural transition in amorphous oxides, including glasses, under extreme compression above megabar pressures (>1 million atmospheric pressure, 100 GPa) results in unique densification paths that differ from those in crystals. Experimentally verifying the atomistic origins of such densifications beyond 100 GPa remains unknown. Progress in inelastic X-ray scattering (IXS) provided insights into the pressure-induced bonding changes in oxide glasses; however, IXS has a signal intensity several orders of magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 68 publications
(162 reference statements)
1
31
1
Order By: Relevance
“…The detailed analysis of the O K ‐edge IXS features of MgSiO 3 glasses combined with the ab initio MD simulations revealed the densification of the depolymerized silicate magmas at the lowermost mantle. Recent IXS studies on simple oxide crystals and glasses have revealed that overall shifts in the O K ‐edge features, particularly shifts in the edge onset energy serve as structural proxies of the interatomic distances and bulk densities (Lee et al, , ; Yi & Lee, , ). For the MgSiO 3 glasses, Figure a presents the systematic shifts in the edge energy at the center of gravity ( E c ) values of the MgSiO 3 crystals (Yi & Lee, , ), glasses (Lee et al, ), and liquids with increasing density.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The detailed analysis of the O K ‐edge IXS features of MgSiO 3 glasses combined with the ab initio MD simulations revealed the densification of the depolymerized silicate magmas at the lowermost mantle. Recent IXS studies on simple oxide crystals and glasses have revealed that overall shifts in the O K ‐edge features, particularly shifts in the edge onset energy serve as structural proxies of the interatomic distances and bulk densities (Lee et al, , ; Yi & Lee, , ). For the MgSiO 3 glasses, Figure a presents the systematic shifts in the edge energy at the center of gravity ( E c ) values of the MgSiO 3 crystals (Yi & Lee, , ), glasses (Lee et al, ), and liquids with increasing density.…”
Section: Resultsmentioning
confidence: 99%
“…The IXS spectra were collected by scanning the X‐ray energy relative to the analyzer energy of 9.9045 keV. Scattered photons were collected at a scattering angle of 25° with a polycapillary post sample collimator, together with a single spherical Si(555) analyzer operating in a backscattering geometry (Chow et al, ; Lee et al, ). The O K ‐edge IXS spectra for MgSiO 3 glasses with varying pressures up to 130 GPa were collected with the step size and the energy loss (incident energy − analyzed energy) range of 0.5 eV and from 530 to 565 eV, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations